Analysis of Factors Affecting Economic Growth in Developing Countries - Mensah, Kofi (Raudhah Publisher, 2024)
Economic growth in developing countries is often influenced by a variety of complex and interrelated factors. This study aims to analyze the main factors that affect economic growth in developing countries. The research issue focuses on how variables such as foreign investment, education, infrastructure, and government policies affect economic growth. To achieve this goal, this study uses a qualitative method that involves literature study and secondary data analysis from economic reports, academic journals, and policy documents. Data is collected from trusted sources covering a wide range of developing countries. The analysis was carried out with a thematic approach to identify patterns and relationships between these factors. The results of the study show that foreign direct investment, improving the quality of education, and infrastructure development have a significant impact on economic growth. In addition, government policies that support innovation and economic reform have also been proven to contribute to better economic growth. However, the results of the study also reveal that challenges such as political instability and corruption can hinder the potential for economic growth despite the presence of positive factors. These findings provide important insights for policymakers in developing countries to design effective strategies to spur sustainable economic growth.